Effects of varied nutrient regimes on soil health and long-term productivity in a rice–wheat system: insights from a 29-year study in the mollisols of the Himalayan Tarai region - Bhatt, Manoj Kumar; Singh, D. K.; Raverkar, K. P.; Chandra, Ramesh; Pareek, Navneet; Dey, Prithwiraj; Pramanick, Biswajit; Joshi, Hem Chandra; Kumar, Mukesh; Gaber, Ahmed; Alsuhaibani, Amnah Mohammed; Hossain, Akbar (Frontiers in Sustainable Food Systems, 2023)
The maintenance of sustainability and quantification of soil health in the rice–wheat system in the Himalayan tarai region is of utmost importance, and a long-term study can properly demonstrate what needs to be done to achieve this. The current study was conducted after the completion of a 29-year crop cycle in the rice–wheat system in 2015 at Pantnagar. Since the beginning of the experiment in 1984, various NPK combinations with or without Zn and farmyard manure (FYM) applications were maintained in a fixed layout along with an absolute control plot without any external nutrition. FYM at 5 mg ha−1 and Zn at 5 kg ha−1 were applied in only rice, and NPK-chemical fertilizers were applied both in rice and wheat. The results revealed that the application of N at 120 kg ha−1 + P at 40 kg ha−1 + K at 40 kg ha−1 + FYM at 5 mg ha−1 + Zn at 5 kg ha−1 (NPK + FYM + Zn) resulted in the maximum attainment of long-term system productivity and the sustainable yield index (SYI), which were 22% higher than those with NPK application. NPK + FYM + Zn and NPK + FYM also improved the soil's overall physical, chemical, and biological parameters. Soil organic carbon, dehydrogenase activity, soil available P and K, phosphate solubilizing bacteria, and actinomycetes were found to be the most important soil quality parameters in Mollisols. From this study, it can be concluded that the application of the recommended NPK along with FYM and Zn can improve soil health and sustain the system productivity of the rice–wheat system in Mollisols of the Himalayan tarai region.